Decision support system for waste management: fuzzy group AHP-CoCoSo - Morteza Yazdani; Chenchui Ye; Mayssam Tarighi Shaayesteh; Pascale Zaraté (International Journal of Production Management and Engineering)
Waste collection and management represents critical strategic focal points in urban development planning. The establishment and maintenance of such systems contribute significantly to policymakers' pursuit of sustainable development objectives. The efficient collection, categorization, and disposal of diverse types of waste pose formidable challenges within urban governance. This study proposes a comprehensive framework for group decision analysis employing Analytic Hierarchy Process (AHP) and Combined Compromise Solution (CoCoSo) to address the optimal site selection problem for waste disposal facilities. In order to rigorously and scientifically address collective waste management issues, this paper engages ten experts to score and evaluate criteria for waste management and alternative site locations. Innovatively integrating Fuzzy methodology with AHP-CoCoSo, the authors optimize decision-makers' preference inputs. Through Fuzzy-AHP, decision-makers' weights and criteria weights are calculated, while Fuzzy-CoCoSo is utilized to determine the final collective decision ranking. By synthesizing the ratings from the ten experts, ideal decision outcomes are obtained to aid cities in selecting the most suitable waste disposal sites. This research contributes to the advancement of urban waste management strategies, offering a systematic approach that accounts for the diverse perspectives of stakeholders and the complex dynamics inherent in waste management decision-making.